Guardians of the Nation? : Economists, Generals, and Economic Reform in Latin America - Castaldi, Ligia De Jesús, 1978- (Book collections on Project MUSE., 2020)
"This new and original study by Ligia Castaldi is the first major publication to analyze in detail the abortion laws of the Latin American and Caribbean nations that are parties to the American Convention on Human Rights. Making use of a broad range of materials relating to human rights and abortion law that are not yet available in English, the first part of this book analyzes how Inter-American human rights bodies have interpreted the American Convention's prenatal right to life. The second part examines Article 4(1) of the American Convention, setting forth a comparative analysis of the laws regarding prenatal rights and abortion in all twenty-three nations that are parties to this treaty. Castaldi questions how Inter-American human rights bodies currently interpret Article (4)1. Against the predominant view, she argues that the purpose of this treaty is to grant legal protection of the unborn child from elective abortion that is broad and general, not merely exceptional. Abortion in Latin America and the Caribbean offers an objective analysis of national and international laws on abortion that presents much valuable information about these laws for the first time in English. Castaldi proposes a new interpretation of the American Convention's right to life provision that is nonrestrictive and provides general protection for the unborn. The book will appeal not only to students and scholars in the field of international human rights but also to human rights advocates more generally"--